A virtual reality application for assessment for attention deficit hyperactivity disorder in school-aged children - Fang Y (Dove Medical Press, 2019)
Yantong Fang,1 Dai Han,1–3 Hong Luo11Children and Adolescents Mental Health Joint Clinic, The Affiliated Hospital of Hangzhou Normal University, Hangzhou, Zhejiang, People’s Republic of China; 2Institutes of Psychological Sciences, Hangzhou Normal University, Hangzhou, Zhejiang, People’s Republic of China; 3Zhejiang Key Laboratory for Research in Assessment of Cognitive Impairments, Hangzhou, Zhejiang, People’s Republic of ChinaBackground and objective: The development of objective assessment tools for attention deficit hyperactivity disorder (ADHD) has become a hot research topic in recent years. This study was conducted to explore the feasibility and availability of virtual reality (VR) for evaluating symptoms of ADHD.Methods: School-aged children were recruited. The children with ADHD or without ADHD were assigned into the ADHD group or Control group, respectively. They were all evaluated using the Conners’ Parent Rating Scale (CPRS), Child Behavior Checklist (CBCL), Integrated Visual and Auditory Continuous Performance Test (IVA-CPT), and a VR test.Results: The correct items, incorrect items, and the accuracy rate of the VR test of the children with ADHD were significantly different with those of the children in the Control group. The correct items, incorrect items, total time, and accuracy of the VR test were significantly correlated with the scores of IVA-CPT (auditory attention and visual attention), CPRS (impulsion/hyperactivity and ADHD index), and CBCL (attention problems and social problems), respectively.Discussion: The results supported the discriminant validity of the VR test for evaluating ADHD in school-age children suffering from learning problems. The VR test results are associated with the commonly used clinical measurements results. A VR test is interesting for children and therefore it attracts them to complete the test; whilst at the same time, it can also effectively evaluate ADHD symptoms.Discussion: The results supported the discriminant validity of the VR test for evaluating ADHD in school-age children suffering from learning problems. The VR test results are associated with the commonly used clinical measurements results. A VR test is interesting for children and therefore it attracts them to complete the test; whilst at the same time, it can also effectively evaluate ADHD symptoms.Keywords: attention deficit hyperactivity disorder, ADHD, virtual reality, VR, Conners’ Parent Rating Scale, CPRS, Child Behavior Checklist, CBCL, Integrated Visual and Auditory Continuous Performance Test, IVA-CPT